Combined Transport Feasibilities in the Zilina Region - Peter Kacala (Communications - Scientific letters of the University of Zilina, 2002)
Combined transport is considered to be one of possible ways of solution of the environment in international transport. The region of Žilina has a suitable geographic location, excellent communication possibilities and a sufficient potential for goods transport in combined transport systems. resulting from its geographical position. Improvement of the economic situation and utilisation of logistics in circulation processes create preconditions for building and efficient exploitation of a modern combined transport terminal as a part of freight village.